Thermal analysis of five-phase PMSG for small-scale wind power application - Kumar R.R.; Singh S.K.; Srivastava R.K.; Saket R.K. (My University, 2025)
Unlike the conventional three-phase PMSG, the five-phase PMSG has a higher power density. This paper presents a lumped parameter thermal model of Five-Phase Permanent Magnet Synchronous Generator (FP-PMSG) for small-scale Wind Energy Conversion (WEC) system. The purpose of this thermal analysis is to use it for the optimal selection of various materials required for development of FP-PMSG. Two methods, namely Finite Element Method (FEM) and Lumped Parameter Model (LPM) applied here for the thermal analysis. The FEM results are more accurate, but time consuming where as LPM provides results in less time. Eight different nodes corresponding to critical parts of the machine are considered in LPM to estimate the temperature of stator yoke, winding, magnet, rotor yoke and shaft under natural cooling. The predicted LPM results are found in good agreement with the simulated FEM, based on which specific materials are identified for various sections of FP-PMSG. © TJPRC Pvt. Ltd.